2011
DOI: 10.1063/1.3622623
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of oxygen vacancy in SrTiO3 and its implications for oxygen-migration-based resistance switching

Abstract: Capacitance−voltage characteristics of high quality Pt Schottky diodes fabricated on oxygen-vacancy-doped SrTiO3 single crystals were used to obtain the oxygen vacancy profiles within one microns of the Pt interface. Computer simulations based on solving the drift-diffusion equations for electrons and ionized vacancies were performed to understand the experimentally observed oxygen vacancy profile’s time-evolution at room temperature and 0 V applied bias. Building upon this understanding, the diode’s room temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 35 publications
2
61
0
Order By: Relevance
“…If we deplete one interface of oxygen vacancies, assymetraic resistive switching should occure. Taking the oxygen vacancy mobility in SrTiO 3 at room temperature (1.5 × 10 -13 cm 2 · v -1 s -1 ), 25 we calculated that 10 hours electrical poling at 90 V can drive oxyen vacancies across the channel and acculumate at the Pt/Ba 0.7 Sr 0.3 TiO 3 interface (inset of Figs. 3(b) and 3(c)).…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…If we deplete one interface of oxygen vacancies, assymetraic resistive switching should occure. Taking the oxygen vacancy mobility in SrTiO 3 at room temperature (1.5 × 10 -13 cm 2 · v -1 s -1 ), 25 we calculated that 10 hours electrical poling at 90 V can drive oxyen vacancies across the channel and acculumate at the Pt/Ba 0.7 Sr 0.3 TiO 3 interface (inset of Figs. 3(b) and 3(c)).…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…Besides the effects of interfaces on the kinetics of oxygen vacancies, there is growing evidence that thermodynamics of oxygen vacancies could also be significantly manipulated by interfaces. [54][55][56] Recent theoretical reports have predicted that vacancy concentration can be controlled via interfacial strain, 57,58 where it has been shown that the formation energy of oxygen vacancies decreases under tensile strain leading to a higher concentration. 58,59 One could thus imagine a strain-controlled oxygen vacancy concentration that could be tuned to the interfacial strain across the adjoining materials as shown in a schematic in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, both heterointerfaces and grain boundaries could be used to control kinetics and thermodynamics of oxygen vacancies. The thermodynamic control would be even more useful as there is a growing appreciation for the critical role of oxygen vacancies [54][55][56] in the physics of interface/thin-film structures based on transition-metal oxides for magnetic and electronic applications. There are also reports of hightemperature superconductivity induced by ordered oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…The breakdown and degradation of devices have limited widespread implementation of these applications for extreme environments. [9][10][11][12][13] The point defect play a significant role in the breakdown and degradation of materials, therefore the defect evolution becomes a major concern in the applications of dielectric and ferroelectric materials. [14][15][16] The defect transports of breakdown and degradation processes have been widely investigated experimentally.…”
Section: Introductionmentioning
confidence: 99%